Automatic lamp with GSM security / Mohd Amirul Hafiz Azman, Ammar Fakrullah Mohd Mokhtar and Muhammad Irfan Khairol Anuar Shah - Azman, Mohd Amirul Hafiz; Mohd Mokhtar, Ammar Fakrullah; Khairol Anuar Shah, Muhammad Irfan (2013)
Auto lamp with GSM security is a combination of automatic lamp control with infra red security and GSM interface. With the aid of this project the user may control the lamp automatically based on the environment and high security with the infra ted and GSM install in the circuit. This project has two LDR sensors. The LDR are controlled b; PICI6F877. This component acts as main part in the circuit. LDR acts when the intensity of the light is changed and the result will be displayed on the seven segments LCD. This project use 12 volts D€ Power supply which is regulated through the adapter.